Multi-use of the white mulberry (Morus alba L.) - Łochyńska, Małgorzata; Oleszak, Grzegorz (Ecological Questions, 2013)
In 2006 Institute of Natural Fibres and Medicinal Plants (INF&MP) began research on an old Polish cultivar of white mulberry - “Żółwińska”. By that time in Europe the white mulberry had been forgotten or known only as a plant associated with breeding of mulberry silkworms. Nevertheless, the initial studies have shown great potential of this plant in energy, food and pharmaceutical industries. The leaves and fruits contain very valuable active substances, which may be used in health care. What is more, very fast growth of mulberry causes that biomass of the plant may be used as biofuel. The aim of the article is promoting the white mulberry and presenting its possible various uses, which may be very useful for several sectors of the European economy.